Caught in a "Bad Romance"? Reconsidering the Negative Association Between Sociosexuality and Relationship Functioning. Issue 9 (22nd November 2017) - Rodrigues, David; Lopes, Diniz; Smith, C. Veronica
Abstract : Sociosexuality refers to individual differences in interest and willingness to engage in sexual activity without an emotional connection. Unrestricted sociosexuality is associated with a greater likelihood of infidelity and with poorer relationship quality. However, previous research has failed to examine relationship-specific characteristics that may moderate these findings. Two studies of romantically involved adults examined whether relationship commitment and different relationship agreement types moderate the associations between unrestricted sociosexuality and infidelity. Study 1 ( N  = 300) showed that individuals in consensual monogamous (CM) relationships with extradyadic sex (EDS) experiences were more sociosexually unrestricted than individuals without such experiences. The positive association between unrestricted sociosexuality and EDS emerged only for less, but not more, committed individuals. Study 2 ( N  = 270) replicated these results. Furthermore, results showed that individuals in consensual nonmonogamous relationships (CNM) relationships were the most sociosexually unrestricted, but no differences emerged in relationship commitment or satisfaction, when compared to individuals in CM relationships without prior EDS. Individuals in CM relationship with prior EDS were the least committed and satisfied. The negative association between unrestricted sociosexuality and both relationship quality indicators emerged for all individuals in CM relationships, but it was nonsignificant for individuals in CNM relationships. Implications are discussed.